Medallion „Librarians in time and space”. Radu R. Rosetti (Confluenţe Bibliologice, 2025)
The article presents the complex figure of the general and academician Radu R. Rosetti, remarkable for his military, cultural and librarianship activity. An erudite personality, Rosetti was decorated for war merits, had an essential role in the founding and management of the National Military Museum and contributed significantly to the organization and modernization of the Library of the Romanian Academy, which he led for two terms. He was elected a full member of the Romanian Academy and distinguished himself through valuable works on military history and librarianship.
Keywords: Rosetti Radu R. (1877 – 1949); Romanian personalities